Regional development of free trade areas in the context of the tax incentive policy of the Manaus free trade zone – Amazonas, Brazil - Cavalcante, Fabio Robson Casara; Paraguassú-Chaves, Carlos Alberto; Fonseca Cavalcante, Ana Maria Morais da; Almeida, Fabrício Moraes de; Moreira Dantas, Lenita Rodrigues; Trindade, Carla Dolezel; Filho, Simão Aznar; Smith, Ruy Drummont; Aznar, Simão Dolezel; Rodrigues Uchôa, Márcia Maria; Uchôa, Marcélio Rodrigues (International Journal of Advanced Engineering Research and Science, 2022)
The research brings in its scope the need to analyze the socioeconomic development of the municipalities of Tabatinga (Amazonas), Guajará-Mirim (Rondônia), Boa Vista and Bonfim (Roraima), Macapá and Santana (Amapá) and Brasiléia (Acre), with extension for the municipality of Epitaciolândia, and Cruzeiro do Sul (Acre), which are subject to the fiscal incentive policy, in the form of Free Trade Areas, linked to the Superintendence of the Manaus Free Trade Zone - SUFRAMA. The general objective of the research was to analyze the regional development of the nine cities covered by the SUFRAMA policy in comparison with other nine Amazonian municipalities not covered by this policy, in order to identify the municipal performances achieved in the face of the Brazilian Amazonian reality. The research method used was hypothetical-deductive. The research data were submitted to the multivariate factor model to extract the scores for the construction of the indices, using the SPSS statistical tool, version 22. The data were submitted to the necessary requirements for the sieve of factorial studies, through the tests of Bartlett's sphericity and the adequacy of the Kaiser-Meyer-Olkin (KMO) sample. In this way, it was possible to build socioeconomic development indexes and, with that, proceed with the due analysis intrinsic to the epistemological question of this work. The data showed adequacy to factor studies and allowed us to observe, in general, the low level of socioeconomic development of the surveyed municipalities, however, with a more favorable situation for the municipalities covered by the SUFRAMA policy.